2020
DOI: 10.1093/infdis/jiaa141
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Interdisciplinary Telehealth Model of Provider Training and Comprehensive Care for Hepatitis C and Opioid Use Disorder in a High-Burden Region

Abstract: Background Hepatitis C virus (HCV) and the opioid epidemic disproportionately affect the Appalachian region. Geographic and financial barriers prevent access to specialty care. Interventions are needed to address the HCV-opioid syndemic in this region. Methods We developed an innovative, collaborative telehealth model in Southwest Virginia featuring bidirectional referrals from and to comprehensive harm reduction (CHR) progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Telehealth is one promising modality that can help expand addiction services via remote administration of addiction treatment [ 35 ]. Telehealth also has the potential to extend addiction services into rural and poor regions where many of our SIRI patients reside postdischarge [ 36 ]. For example, if a patient is not ready to enter recovery during their inpatient stay, having the option to utilize telehealth postdischarge and begin MOUDs when they are ready is invaluable.…”
Section: Discussionmentioning
confidence: 99%
“…Telehealth is one promising modality that can help expand addiction services via remote administration of addiction treatment [ 35 ]. Telehealth also has the potential to extend addiction services into rural and poor regions where many of our SIRI patients reside postdischarge [ 36 ]. For example, if a patient is not ready to enter recovery during their inpatient stay, having the option to utilize telehealth postdischarge and begin MOUDs when they are ready is invaluable.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacists or non-specialist providers may also contribute directly to therapy monitoring either in a clinic or using telehealth systems [ 40 ]. Studies have demonstrated the improved adherence and better prevention of drug–drug interactions and medication errors with the involvement of support staff [ 41 , 42 ]. All patients who complete DAA therapy should be evaluated for SVR at least 12 weeks after completing therapy to confirm the efficacy of therapy and to determine the plan for subsequent clinical follow-up [ 18 , 19 ].…”
Section: Treatment Monitoring and Post-treatment Follow-upmentioning
confidence: 99%
“…Prior studies have shown this to be achievable. 21,22,34,67,68,73,74 For example, a clinical trial in the Washington D.C. area found that patients treated by advanced practice providers or primary care providers given a short 3-hour training had similar treatment outcomes compared to specialists treating chronic HCV. 67 These findings underscore the point also demonstrated in several other studies: chronic HCV can be effectively treated by non-specialists.…”
Section: Loss To Follow-up or Missed Appointmentsmentioning
confidence: 99%
“…67 These findings underscore the point also demonstrated in several other studies: chronic HCV can be effectively treated by non-specialists. 66,71,[73][74][75] To help providers who have not traditionally treated HCV gain more experience, tele-mentoring programs (i.e., Project ECHO® in the U.S.) can be utilized; these programs have been launched worldwide, in places such as Australia, Rwanda, and India. 48,69,[76][77][78][79] These tele-mentoring programs increase primary care provider capabilities and confidence in treating HCV, which leads to more patients being cured of HCV.…”
Section: Loss To Follow-up or Missed Appointmentsmentioning
confidence: 99%